Co-option of signaling mechanisms from neural induction to telencephalic patterning. - Aboitiz, F; Montiel, J (2007)
This article provides an overview of signaling processes during early specification of the anterior neural tube, with special emphasis on the telencephalon. A series of signaling systems based on the action of distinct morphogens acts at different developmental stages, specifying interacting developmental fields that define axes of differentiation in the rostrocaudal and the dorsoventral domains. Interestingly, many of these signaling systems are co-opted for several differentiation processes. This strategy provides a simple and efficient mechanism to generate novel structures in evolution, and may have been especially important in the origin of the telencephalon and the mammalian cerebral cortex. For example, the action of fibroblast growth factor (FGF) secreted in early stages from the anterior neural ridge, but in later stages from the dorsal anterior forebrain, may have been a key factor in the early differentiation of the ventral telencephalon and in the eventual expansion of the mammalian neocortex. Likewise, bone morphogenetic proteins (BMPs) participate at several stages in neural patterning, even if early neural induction consists of the inhibition of the BMP pathway. BMPs, secreted dorsally, interact with FGFs in the frontal aspect of the hemispheres, and with PAX6-dependent signaling sources located laterally, to pattern the dorsal telencephalon. The actions of other morphogens are also described in this context, such as the ventralizing factor SHH, the dorsalizing element GLI3, and other factors related to the dorsomedial telencephalon such as WNTs and EMXs. The main conclusion we draw from this review is the well-known phylogenetic and developmental conservatism of signaling pathways, which in evolution have been applied in different embryological contexts, generating novel interactions between morphogenetic fields and leading to the generation of new morphological structures.